Variable Heat and Mass Transfer Boundary on an Unsteady MHD Flow through a Porous Medium over an Infinite Vertical Plate - , M. Veera Krishna (Archives of Current Research International, 2016)
We have considered the variable heat and mass transfer boundary on an unsteady MHD flow through a loosely packed porous medium over an impulsively started vertical plate. The temperature of plate is made to rise linearly with time. The fluid considered is gray, absorbing-emitting radiation but a non-scattering medium. The governing equations involved in the present analysis are solved by the Laplace-transform technique. The velocity, skin friction, Nusselt number and Sherwood number are obtained and computationally discussed for different governing parameters such as radiation parameter, Schmidt number, Thermal Grashof number, mass Grashof number, magnetic field parameter, porous parameter and Prandtl number with the combination of the other flow parameters are illustrated graphically, and physical aspects of the problem are discussed.